Wearable Textile Antennas: examining the effect of bending on their performance - Ferreira, David (2018)
This article presents a study on the effect of bending on the performance of a rectangular textile-patch antenna operating at a 2.4-GHz industrial, scientific, and medical (ISM) band. The substrate of the antenna was made from denim textile, and the conducting layers were made from a copper and nickel plated polyester fabric. A parametric study was made to determine the influence of an antenna bending around its length and width on its performance parameters in chest, leg, arm, or wrist integration for wireless body-area network (WBAN) scenarios. Results were obtained from bench and anechoic chamber measurements and compared with simulation results. The prototype presents a maximum gain of approximately 4 dBi and 70° of half-power beamwidth (HPBW) in the flat position. When subjected to a wrist equivalent bending, the gain decreases by 2 dB, HPBW has an increase of about 25°, and front-to-back radiation ratio decreases. Mean and standard deviation parameters as a function of bending curvature were calculated from parametric simulations.